Assessing the Impact of Energy Sources and Macroeconomic Factors on Environmental Sustainability: Evidence from South Africa - Hlongwane, Nyiko Worship; Khobai, Hlalefang; Ralarala, Ombeswa (International Journal of Energy Economics and Policy, 2026)
This study examines the role of energy sources and macroeconomic factors in environmental sustainability in South Africa, utilizing time series data from 1985 to 2024. The primary objective is to investigate the impact of different energy sources, electricity prices, economic growth, population growth, and inflation on CO2 emissions and greenhouse gas emissions. The study employs Vector Error Correction Model (VECM) and Autoregressive Distributed Lag (ARDL) models to analyze the short-run and long-run relationships between energy consumption, energy generation, economic growth, and environmental sustainability. The key findings indicated that a negative statistically significant relationship exists between electricity prices and CO2 emissions in the short run, but electricity prices increase greenhouse gas emissions in the long run. Renewable energy has a significant negative impact on CO2 and greenhouse gas emissions, promoting environmental sustainability. Economic growth increases CO2 and greenhouse gas emissions, supporting the Environmental Kuznets Curve hypothesis. Population growth increases CO2 and greenhouse gas emissions in the long run. Nuclear power has a positive impact on CO2 and greenhouse gas emissions, contradicting some previous studies. The study’s policy recommendations include implementing pricing mechanisms that encourage energy conservation and reduce emissions. Investing in renewable energy sources like solar and wind power to reduce dependence on non-renewable energy. Promoting sustainable economic growth by investing in green technologies and implementing policies that balance economic development with environmental protection. Developing strategies to manage population growth and its impact on the environment. Implement policies to mitigate the impacts of climate change and promote a green economy.